2005
DOI: 10.1093/eurpub/cki018
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation and hospital utilization for tuberculosis in Russia: hospitals as social care institutions

Abstract: As hospitalizations of tuberculosis patients in colder months fulfil an important social need, shifts to ambulatory care must be carefully managed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 6 publications
3
31
0
Order By: Relevance
“…[7] Present study results were consistent with another studies which found that majority of the hospitalized patients were males i.e. 69% [8] and 58.4%. [9] A study [10] reported that 20% of the patients were using safe sputum disposal technique and 46.7% were covering their mouth while coughing and Another study [11] founds that 61% of the patients were covering their mouth while coughing, which was inconsistent with the results of present study.…”
Section: Discussionsupporting
confidence: 92%
“…[7] Present study results were consistent with another studies which found that majority of the hospitalized patients were males i.e. 69% [8] and 58.4%. [9] A study [10] reported that 20% of the patients were using safe sputum disposal technique and 46.7% were covering their mouth while coughing and Another study [11] founds that 61% of the patients were covering their mouth while coughing, which was inconsistent with the results of present study.…”
Section: Discussionsupporting
confidence: 92%
“…It is quite possible that private hospitals in Greece are more efficient than public hospitals because of competitive pressures. However, empirical evidences reported by other studies showed that private hospitals do not appear to be more cost efficient than public hospitals 9 . Rivers and Bae [48] examined hospital competition in major metropolitan areas in the USA.…”
Section: Economies Of Scale and Economies Of Scopementioning
confidence: 89%
“…If the hospital cost function is misspecified, then hospitals will 9 Even in the USA where most of the health care is privately provided, hospitals do not promote efficiency. Dafny [47] argued that as long as health care providers can earn non-negative profits, there is very little incentive to reduce costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceived disease focus (as opposed to holistic focus) of DOTS is problematic in the Russian context where the traditional public health approach to tuberculosis, through institutional structures, attempts to resolve the many concomitant social problems that many patients present with [39,40].…”
Section: Discussionmentioning
confidence: 99%